Analysis of problems in planning and organizing independent curriculum in madrasah ibtidaiyah: teacher's perspective - Sigiyuwanta, Recsatasha; Mustiningsih, Mustiningsih; Nurabadi, Ahmad (Universitas Kanjuruhan Malang, 2024)
The Merdeka Curriculum, as the latest innovation in the world of Indonesian education, raises a number of problems in the process of implementing it in Madrasah Ibtidaiyah, especially for teachers. This article analyzes the problems that arise, especially related to curriculum planning and organization. The method used is a descriptive survey, data were collected from teachers at Madrasah Ibtidaiyah Negeri 2 Trenggalek. The results showed that the majority of respondents had a lack of understanding of the independent curriculum, difficulties in preparing documents and learning tools for the independent curriculum, inadequate facilities and infrastructure. Lack of participation in intensive training and technical guidance results in a lack of understanding of the substance of the curriculum being the main factor behind this problem. In the face of these challenges, a number of alternative solutions were proposed, including intensive training, comparative studies, teacher working groups, and improved technological facilities and infrastructure